Nuva Adaptation Mechanism of Salt Farmers in Facing Climate Change: Case Study in Indramayu, West Java - Nuva, Nuva; Rahma, Azkia; Fauzi, Akhmad (ProBisnis : Jurnal Manajemen, 2025)
Climate change has become a serous threat to the environment and the society, especially for coastal communities that depend on the fisheries sector for their livelihoods, both fishing and cultivation. Salt production is a livelihood that is sensitive to the impacts of climate change because the salt production process is greatly influenced by natural factors. The impact of climate change affects the livelihoods of salt farmers' households. In dealing with climate change, a series of resilience measures are taken so that household livelihoods can continue to be maintained. To meet household needs, salt farmers carry out several adaptations such as converting pond land, seeking income outside salt ponds, and renting out pond land. The purpose of this study was to examine the adaptation mechanisms of salt farmers' households to the effects of climate change. This study was analyzed using quantitative descriptive analysis to answer the adaptation mechanisms of salt farmers. The adaptive capacity of salt farmers is divided into three types, namely the capacity to learn, buffer capacity, and. The capacity to regulate oneself, The results showed that the adaptive capacity of salt farmers who had the highest percentage in the form of past experience inspired new ways to increase household income of salt farmers, knowledge of salt farmers and the interest of salt farmers to participate in training and strong trust between farmers,